The 110-kD protein-calmodulin complex of the intestinal microvillus (brush border myosin I) is a mechanoenzyme (The Rockefeller University Press, 1989)
The 110-kD protein-calmodulin complex (110K-CM) of the intestinal brush border serves to laterally tether microvillar actin filaments to the plasma membrane. Results from several laboratories have demonstrated that this complex shares many enzymatic and structural properties with myosin. The mechanochemical potential of purified avian 110K-CM was assessed using the Nitella bead motility assay (Sheetz, M. P., and J. A. Spudich. 1983. Nature (Lond.). 303:31-35). Under low Ca2+ conditions, 110K-CM-coated beads bound to actin cables, but no movement was observed. Using EGTA/calcium buffers (approximately 5-10 microM free Ca2+) movement of 110K-CM-coated beads along actin cables (average rate of approximately 8 nm/s) was observed. The movement was in the same direction as that for beads coated with skeletal muscle myosin. The motile preparations of 110K-CM were shown to be free of detectable contamination by conventional brush border myosin. Based on these and other observations demonstrating the myosin-like properties of 110K-CM, we propose that this complex be named "brush border myosin I."